Development of a novel zero point setting device for high speed and micro machining applications - Amin, A. K. M. Nurul; Mahmud, Md. Asif; Arif, Muammer Din; Derus, Nur Hidayah; Khamis, Siti Salwa (2012)
In CNC machining, high downtimes of machine tools are associated with the tool zero point setting in the absence of automatic setting devices. The problem is more acute in high speed and micro-machining processes dealing with micron and sub micrometer range depth of cut which precise require zero point setting. Hence there is a high demand for reliable and cost-effective zero-point setting devices. The majority of conventional, and some CNC, machine-tools do not have an integrated zero point setting device. Therefore, the determination of the zero point during metal cutting is currently done by a trial and error method and the accuracy of positioning of the tool especially in the case of micro-machining is not satisfactory and poses a challenging problem. The available zero point setting devices are extremely sophisticated electronic instruments, which are very expensive with unit prices ranging up to US$ 30,000. Also, the operation of such devices demands very skilled machinists and trained operators. The novel zero-point setting system, developed by the authors, uses the available equipments in a normal machining laboratory to detect the zero point with a good degree of accuracy and repeatability. One of the terminals of the device is connected to the tool holder and the other to the work-piece fixture using screws. When physical contact is established, between the tool and the work-piece/fixture element, a flashing LED light and a sounding buzzer are activated indicating that the circuit has been closed and the tool zero point is attained. The electric circuit arrangement of the device ensures high sensitivity to actual physical contact and a minimum resolution which is equal to the relevant machine’s minimum move (less than 0.1 μm for grinding operations). Thus, this device can play a vital role for precisely setting the zero point (or starting point) for micro-machining, and reducing the non-productive downtime of machine-tools and extra training of the relevant personnel. The total expenditure for the construction of this device was about RM 50 and it can be easily attached to vertical and horizontal milling machines, drilling machine, grinders, lathes, or machining centers. It can also be used with non-conductive work-pieces like glass, plastic and ceramics. Therefore, with this cost effective, reliable, and accurate device it is possible to make manufacturing processes more precise, rapid, economical, and productive.